Problems of Developing Effective Corporate Strategies by an International Company - Ruipiao Lian; Alexey Chernov (Communications of International Proceedings, 2021)
A characteristic feature of the modern management of international companies is the increased attention to the strategic aspects of management associated with solving the problem of constant development of the company in accordance with the dynamically changing conditions of the external environment. Therefore, strategic management plays a significant role in the management of the company in the international market. The relevance of strategic management lies in the fact that no company can successfully survive in a competitive environment if it does not have clearly defined benchmarks, directions that set what it strives for, what it wants to achieve in its activities.
Keywords: Corporate strategy; information technology; international company; cloud technologies; business processes; concentrated growth strategy.